PENERAPAN SISTEM INFORMASI PENDAFTARAN UJI KOMPETENSI BERBASIS WEB PADA LSP PERDAGANGAN RITEL SEMARANG - Ardiansah, Muhammad Noor (Universitas Negeri Semarang, 2020)
The increase in requests for competency testing by LSP cannot all be further processed because complicated verification and feasibility stages of the assessee result for an effective and efficient system. The application of information systems to support the management of competency tests effectively, efficiently and economically. This service is carried out by stages: socialization, review of conditions, information system design and restatement of information systems. Outputs include: (1) LSP managers appreciate the information system in LSP Retail competency test activities, in addition to being integrated with the main retail LSP site, also providing benefits about efficiency, effectiveness and accessibility, (2) there is conformity of information system features and flow which is high with the competency test process in LSP Retail, (3) the security and privacy aspects of access data maintained by changes in domain and site security features through changes in the site domain and (4) the carrying capacity of the information system in the LSP Retail is carried out by the manager of the LSP Retail the site's special administrator to be well maintained.